A STUDY OF EMOTIONAL MARKETING IN CHANGING CONTEXT OF INDIAN PRODUCT ADVERTISEMENTS: THE NATIONALISM PERSPECTIVE IN INDIA 2020 - Dr O P Yadav, Dr Gautam Jaiswal (International Journal of Advanced Science and Technology, 2020)
‘India 2020’ was a dream of many Nobel Indians. Lots of changes were anticipated in Indian context. Many of them were completed and much more is expected in coming years. Clean India green India was a vision for our nation, digital India was another dream for the year 2020. Many of these dream come true. But In this make in India era Indians have developed a feeling of Nationalism. Different activities by army and their achievements on enemy have developed this feeling at another stage.